1996
DOI: 10.1006/viro.1996.0218
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Receptor-Binding Regions of pb5 Proteins of Bacteriophages T5 and BF23

Abstract: The receptor-binding protein pb5(T5) of bacteriophage T5, when expressed from the oad gene cloned in pVK88 under the control of the phage T7 promoter/polymerase system, has been shown to bind to its FhuA receptor on the surface of E. coli, where it blocks FhuA for subsequent adsorption of T5 (Mondigler et al., FEMS Microbiol. Lett., 130, 293-300, 1995). In the present study the blocking assay has been applied to analyze the effects of several mutations within oad on the FhuA-binding properties of corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…These genomic homologies identified the H8 receptor-binding tail protein (Rbp), and its comparison to the T5 and BF23 receptor binding proteins revealed regions that likely interact with the OM proteins FepA, FhuA, and BtuB, respectively. These data support and refine prior predictions of the T5 receptor binding domain in the oad structural gene (63). The analogous portion of the H8 Rbp, from residues 138 to 213, has a net charge of Ϫ8, consistent with the experimental evidence that H8 interacts with FepA in a similar way as the acidic siderophore FeEnt.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…These genomic homologies identified the H8 receptor-binding tail protein (Rbp), and its comparison to the T5 and BF23 receptor binding proteins revealed regions that likely interact with the OM proteins FepA, FhuA, and BtuB, respectively. These data support and refine prior predictions of the T5 receptor binding domain in the oad structural gene (63). The analogous portion of the H8 Rbp, from residues 138 to 213, has a net charge of Ϫ8, consistent with the experimental evidence that H8 interacts with FepA in a similar way as the acidic siderophore FeEnt.…”
supporting
confidence: 86%
“…For H8, the Rbp is most homologous to Hrs and pb5 (Oad) of BF23 and T5, respectively, and Tpf is related to the pb2 (D18-19) of T5. Despite the fact that the products of oad and hrs may functionally replace each other in the tails of T5 and BF23, respectively (39, 48), Mondigler et al (62,63) reported that no homology exists between these genes. The CLUSTAL W alignment of the T5, BF23, and H8 receptor binding proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the large size of the phage particles relative to the other ligands may in some manner preclude the enhancement of FhuA-TonB interaction as detected in vitro. The identification and isolation of tail fiber proteins that constitute the minimal requirement for phage to participate in receptor recognition (54,55) will assist in the analysis of TonB coupling with TonB-dependent receptors. Future studies need to focus upon the ligand-induced conformational dynamics of FhuA which govern its physical association with TonB and upon those regions of FhuA which are required for the interaction with TonB.…”
Section: Discussionmentioning
confidence: 99%
“…However, this previous assignment must be revisited as pb2 is not long enough to extend from the bottom of the tail tube to the end of the central fiber (18). pb5, the receptor binding protein (RBP), ensures the binding of T5 to its receptor, the E. coli outer membrane protein FhuA (19,20). The FhuA-pb5 complex has been characterized in vitro (21)(22)(23), but the exact location of pb5 at the tail tip remains uncertain.…”
mentioning
confidence: 99%